Highly Stable and Stretchable Conductive Films through Thermal‐Radiation‐Assisted Metal Encapsulation - Liu, Zhiyuan; Wang, Hui; Huang, Pingao; Huang, Jianping; Zhang, Yu; Wang, Yuanyuan; Yu, Mei; Chen, Shixiong; Qi, Dianpeng; Wang, Ting; Jiang, Ying; Chen, Geng; et al. (Advanced materials (Weinheim), 2019)
Stretchable conductors are the basic units of advanced flexible electronic devices, such as skin‐like sensors, stretchable batteries and soft actuators. Current fabrication strategies are mainly focused on the stretchability of the conductor with less emphasis on the huge mismatch of the conductive material and polymeric substrate, which results in stability issues during long‐term use. Thermal‐radiation‐assisted metal encapsulation is reported to construct an interlocking layer between polydimethylsiloxane (PDMS) and gold by employing a semipolymerized PDMS substrate to encapsulate the gold clusters/atoms during thermal deposition. The stability of the stretchable conductor is significantly enhanced based on the interlocking effect of metal and polymer, with high interfacial adhesion (>2 MPa) and cyclic stability (>10 000 cycles). Also, the conductor exhibits superior properties such as high stretchability (>130%) and large active surface area (>5:1 effective surface area/geometrical area). It is noted that this method can be easily used to fabricate such a stretchable conductor in a wafer‐scale format through a one‐step process. As a proof of concept, both long‐term implantation in an animal model to monitor intramuscular electric signals and on human skin for detection of biosignals are demonstrated. This design approach brings about a new perspective on the exploration of stretchable conductors for biomedical applications. Thermal‐radiation‐assisted metal encapsulation is used to prepare large‐scale high‐performance stretchable conductors that possess high stretchability, stability and adhesion and large surface area. They are used to simultaneously monitor electromyography and skin deformation and implanted to detect intramuscular signals. This study offers a new path for highly stable stretchable conductors and related biointerface applications.